The Effect Of Expert Management, Professional Skepticism And Professional Ethics On Auditors Detecting Ability With Emotional Intelligence As Modeling Variables (Study At The Makassar City Inspectorate) - Murtiadi Awaluddin; Nirgahayu; Rulyanti Susi Wardhani (International Journal of Islamic Business and Economics (IJIBEC), 2019)
This study aims to examine the effect of management experts, professional skepticism and professional ethics on the auditor's ability to detect fraud with intelligence emotional as a moderating variable. This research was conducted at the Makassar City Inspectorate. This research is an explanatory study with a quantitative approach. The study used a saturated sample method with a sample of 25 people. Analysis data in this research using multiple regression analysis with absolute difference value. The results of multiple analysis show that management experts, professional skepticism and professional ethics have a positive and significant effect on the auditor's ability to detect fraud. The result of the analysis show that emotional intelligence is able to moderate expert management and professional skepticism towards the auditor's ability to detect fraud, while emotional intelligence does not moderate professional ethics on the auditor's ability to detect fraud.